CUSTOMER RELATIONSHIP MANAGEMENT (CRM) JASA PENDIDIKAN ISLAM TRANSFORMATIF DI MADRASAH IBTIDAIYAH EL-RAHMAH KOTA SURABAYA - Syamsuddin, Haris; Indarti, Luluk; Syaifullah, Achmad Faisol (TARBAWI:Journal on Islamic Education, 2023)
AbstractCustomer Relationship Management (CRM) is a communication strategy that places educational institutions or service providers as subjects and consumers or students with guardians as users of educational institution services as objects. In this context, information and communication technology becomes an important part of the management process. One of them is improving services with the concept of Customer Relationship Management (CRM). This study uses a descriptive qualitative approach with a case study design. The results of this study are that the implementation of Customer Relationship Management (CRM) is carried out by building awareness of the importance of education, especially reciting the Koran through regular meetings with guardians of students and a personal approach with guardians of students, building good cooperation with guardians of students, government and private institutions, utilizing social media (Wa groups, Instagram, Facebook, Youtube and Website) to provide information and as a medium of communication between madrasahs and the community, especially guardians of students.